A perspective on the symptoms and causes of the financial crisis - Cabral, Ricardo (2019)
This article identifies two paradoxes prior to the onset of the financial crisis: banking profits were at historically high levels despite the impending crisis; and though profits were high the profitability of financial intermediation was poor. Using a novel model of banking, it argues that large banks attained high profits through balance sheet expansion and growing mismatches between assets and liabilities. As a result, large banks’ financial leverage rose while their liquidity structure worsened, setting the conditions for a systemic banking crisis. Finally, this article argues that this conduct and performance was only possible due to misguided changes to the regulatory framework, specifically the Basel I Capital Accord and reductions in reserve requirements.